Anomalous efficiency elevation of quantum-dot light-emitting diodes induced by operational degradation - Siyu He; Xiaoqi Tang; Yunzhou Deng; Ni Yin; Wangxiao Jin; Xiuyuan Lu; Desui Chen; Chenyang Wang; Tulai Sun; Qi Chen; Yizheng Jin (Nature Communications, 2023)
Abstract Quantum-dot light-emitting diodes promise a new generation of high-performance and solution-processed electroluminescent light sources. Understanding the operational degradation mechanisms of quantum-dot light-emitting diodes is crucial for their practical applications. Here, we show that quantum-dot light-emitting diodes may exhibit an anomalous degradation pattern characterized by a continuous increase in electroluminescent efficiency upon electrical stressing, which deviates from the typical decrease in electroluminescent efficiency observed in other light-emitting diodes. Various in-situ/operando characterizations were performed to investigate the evolutions of charge dynamics during the efficiency elevation, and the alterations in electric potential landscapes in the active devices. Furthermore, we carried out selective peel-off-and-rebuild experiments and depth-profiling analyses to pinpoint the critical degradation site and reveal the underlying microscopic mechanism. The results indicate that the operation-induced efficiency increase results from the degradation of electron-injection capability at the electron-transport layer/cathode interface, which in turn leads to gradually improved charge balance. Our work provides new insights into the degradation of red quantum-dot light-emitting diodes and has far-reaching implications for the design of charge-injection interfaces in solution-processed light-emitting diodes.